Beispiel Nr: 02
$ \text{Gegeben:} \\ \text{Vektoren: } \vec{A} =\left( \begin{array}{c} a_1 \\ a_2 \\ a_3 \\ \end{array} \right) \quad \vec{B} =\left( \begin{array}{c} b_1 \\ b_2 \\ b_3 \\ \end{array} \right) \\ \\ \text{Gesucht:} \\ \text{Länge der Vektoren:} \\ \text{Fläche des Parallelogramms} \\ \text{Vektorprodukt} \\ \text{Skalarprodukt} \\ \text{Lineare Abhängigkeit von 2 Vektoren}\\ \\ \\ \textbf{Gegeben:} \\ \text{Vektor: } \vec{A} =\left( \begin{array}{c} 2 \\ 1 \\ -4 \\ \end{array} \right) \quad \vec{B} =\left( \begin{array}{c} -2 \\ -1 \\ 4 \\ \end{array} \right) \\ \\ \\ \textbf{Rechnung:} \\ \text{Vektoren: } \vec{a} =\left( \begin{array}{c} 2 \\ 1 \\ -4 \\ \end{array} \right) \quad \vec{b} =\left( \begin{array}{c} -2 \\ -1 \\ 4 \\ \end{array} \right) \\ \bullet \text{Länge der Vektoren:} \\ \left|\vec{a}\right| =\sqrt{a_1^2+a_2^2+a_3^2} \\ \left|\vec{a}\right| =\sqrt{2^2+1^2+\left(-4\right)^2} \\ \left|\vec{a}\right| =4,58 \\ \left|\vec{b}\right| =\sqrt{b_1^2+b_2^2+b_3^2} \\ \left|\vec{b}\right| =\sqrt{\left(-2\right)^2+\left(-1\right)^2+4^2} \\ \quad \left|\vec{b}\right| =4,58 \\ \bullet \text{Skalarprodukt:} \\ \vec{a} \circ \vec{b}=2 \cdot -2 + 1 \cdot -1 -4 \cdot 4 = -21 \\ \bullet \text{Vektorprodukt:} \\ \vec{a} \times \vec{b}= \left( \begin{array}{c} 1 \cdot4-\left(-4\right)\cdot\left(-1\right) \\ -4\cdot\left(-2\right)-4\cdot2 \\ 2\cdot\left(-1\right)-1\cdot\left(-2\right) \\ \end{array} \right) \\ \vec{c} = \vec{a} \times \vec{b}= \left( \begin{array}{c} 0 \\ 0 \\ 0 \\ \end{array} \right) \\ \bullet \text{Fläche des Parallelogramms} \\ \left|\vec{c}\right| =\sqrt{0^2+0^2+0^2} \\ \left|\vec{c}\right| =0 \\ \bullet \text{Schnittwinkel:} \\ \cos \alpha= \displaystyle\frac{ \vec{a} \circ \vec{b}}{ \left|\vec{a}\right| \cdot \left|\vec{b}\right|}\\ \cos \alpha= \left|\displaystyle\frac{-21}{4,58 \cdot 4,58} \right| \\ \cos \alpha= \left| -1 \right| \\ \alpha=0 \\ \bullet \text{Lineare Abhängigkeit von 2 Vektoren}\\ \left( \begin{array}{c} 2 \\ 1 \\ -4 \\ \end{array} \right) =k \cdot \left( \begin{array}{c} -2 \\ -1 \\ 4 \\ \end{array} \right) \\ \begin{array}{cccc} 2&=&-2 k & \quad /:-2 \quad \Rightarrow k=-1 \\ 1&=&-1 k & \quad /:-1 \quad \Rightarrow k=-1 \\ -4&=&4 k & \quad /:4 \quad \Rightarrow k=-1 \\ \end{array} \\ \\ \Rightarrow \text{Vektoren sind linear abhängig - parallel}\\ $